Towards the establishment of collaboration between the Ramon Magsaysay (Cubao) High School Library and the Quezon City Public Library - Diaz, Chad Aren E. (2013)
Helping provide a functionally-literate society is one of the ultimate goals of both school and public libraries. However, realization of the said goal is hindered by the different issues the libraries face such as inadequate resources and budget, poor library services, and absence of a licensed librarian. Collaboration, the act of working together that includes establishment of joint goal and vision, is seen as an answer to address the said issues, hence, helping school and public libraries improve.